Accuracy of Fetuin-A in Predicting Hemodialysis in Diabetic and Non-Diabetic Patients - Mahmoud saad Abdel Aleem; Atef Farouk El Akad; Ali Mohammad Ali Hasan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Diabetes mellitus (DM) has routinely been described as a metabolic disorder characterized by hyperglycemia that develops because of defects in insulin secretion, insulin action, or both Aim:To explore the accuracy of fetuin in predicting hemodialysis in diabetic and non-diabetic patient. Patients and methods: This case-control control trial was performed at the Internal Medicine Department, Minia University Hospital during the period from June 2024 to February 2025. The study included a total of 45 subjects who were classified to group (I) included 15 healthy subjects (non-diabetic and not on hemodialysis) served as control group (Control group), group (II), included 15 non-diabetic patients on hemodialysis (HD group) and group (III) included 15 diabetic patients on hemodialysis (DM+HD group). Results: The sensitivity of using Fetuin-A to predict hemodialysis was 93.3%, specificity was 72%, positive predictive value was 66.7%, negative predictive value was 94.7% and accuracy was 80%. The sensitivity of using Fetuin-A to predict hemodialysis among patients with diabetes was 93.3%, specificity was 73.3%, positive predictive value was 77.8%, negative predictive value was 91.7% and accuracy was 83.3% Conclusion: Fetuin-A was significantly higher in diabetic patients on hemodialysis compared to non-diabetic patients on hemodialysis and the normal healthy subjects, Furthermore, fetuin-A is reliable and accurate biomarker in predicting hemodialysis in diabetic and non-diabetic patients.